Tahapan Membangun Tim Business Analytics yang Sukses - Irvan Bravely (Universitas Pahlawan Tuanku Tambusai, 2022)
The business analytics team is the initial foundation for how business analytics can increase an organization's competitive advantage. Competitive advantage can be achieved because business analytics analyzes the organization's key data metrics so that stakeholders are able to make careful decisions that provide greater value for the organization. Three important things that need to be done when forming a business analytics team are: identifying business needs; forming a team; and involving stakeholders. It is hoped that this research will be able to provide understanding regarding building a business analytics team to organizations and academics.